Determinants of Islamic Financial Literacy Index: Comparison Based on Ethnographic Studies in Yogyakarta, Indonesia - Miftakhul Khasanah; Rizki Aminullah; Dewi Setianingsih (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
This paper aims to determine the level of Islamic financial literacy (IFL) and identify factors that have a relationship and influence on the level of IFL in various communities. The research was conducted because there have been inconsistencies in previous studies regarding the factors that influence the level of financial literacy, both general and Islamic financial literacy. Demographic factors such as gender, education level, and income level are often used in this type of research. This paper is compiled in two steps with mixed method. The first calculates the IFL index level, and the second analyzes the factors affecting the IFL index level using ethnographic studies. Islamic financial literacy indicators consist of knowledge, skills, beliefs, attitudes, and behavior based on the aspects of religiosity and Maqasid al-Shari'ah. The factors that influence the Islamic financial literacy index are determined using ethnographic studies. The result is the education level affects the financial literacy index in one community. But the results will be different when different communities are compared. One of the influencing factors is the financial socialization agent, and this is very closely related to the political socialization theory. In this case, the Bank or Islamic financial institution acts as a potential agent.